2021
DOI: 10.1108/apjba-05-2021-0200
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity traits and the rational cognitive process of entrepreneurship: empirical evidence from Vietnam

Abstract: PurposeThis study aims to integrate predictions from clinical psychology and UPPS impulsivity with the theory of planned behaviors (TPB) to draw a conceptual framework and test the prediction that attention deficit hyperactivity disorder (ADHD) symptoms, impulsivity would contribute to the prediction of the reasoned cognitive process of entrepreneurship over and above key predictors from an extended TPB model.Design/methodology/approachThis study utilized a sample of 2,482 students from 14 universities/institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 74 publications
0
44
0
Order By: Relevance
“…It is considered one of the most applied theories in the social and behavioral sciences and is also often applied in public health and political science (Nguyen, 2019). Intentions to conduct a certain behavior are hypothesized to catch a person's decision to carry out an actual action and show their incentives to involve in this action (Doan et al, 2021). Krueger and Carsrud (1993) argue that intentions are defined as the cognitive state that instantly before performing behaviors.…”
Section: Theoretical Framework 21 the Theory Of Planned Behavior And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered one of the most applied theories in the social and behavioral sciences and is also often applied in public health and political science (Nguyen, 2019). Intentions to conduct a certain behavior are hypothesized to catch a person's decision to carry out an actual action and show their incentives to involve in this action (Doan et al, 2021). Krueger and Carsrud (1993) argue that intentions are defined as the cognitive state that instantly before performing behaviors.…”
Section: Theoretical Framework 21 the Theory Of Planned Behavior And ...mentioning
confidence: 99%
“…The TPB is identified as a social cognition model which is often used to investigate a reasonable decision involved in assessing the advantages and disadvantages of estimated outcomes (Ajzen, 2020). It is a well-formed theory to investigate and predict human behavior broadly via the various aspects of life domains (Doan et al, 2021), such as whistleblowing (Sarikhani and Ebrahimi, 2021), employee involvement (Dawkins and Frass, 2005) and proenvironmental purchase behaviors (Nguyen, 2019). Moreover, a body of meta-analyses confirmed that the TPB can be appropriately applied to predict intentions and behaviors to become entrepreneurs (Schlaegel and Koenig, 2013;Gorgievski et al, 2017).…”
Section: Moderating Effects Of Covid-19 Distressmentioning
confidence: 99%
“…The TPB (Ajzen, 1991), which endeavours to determine the precursors of a certain behaviour, has been broadly used to explain various actions (Ajzen, 2020). Intention to perform a specific behaviour is hypothesised to apprehend a person's decision to carry out an action and reflect his or her motivations to be involved in this behaviour (Doan et al, 2021). Ajzen (2020) argues that intentions are defined as the cognitive state that occurs instantly prior to performing behaviours.…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%
“…The interrelationships of the three core dimensions in the TPB and entrepreneurial intention have been investigated by a body of prior scholars (Zaremohzzabieh et al, 2019). Nevertheless, the influence of subjective norms on business venturing intention is not clear (Doan et al, 2021). Indeed, several scholars have suggested that subjective norms have a strong influence on entrepreneurial intention (Maresch et al, 2015), while others have claimed that this link is very weak or not statistically significant (Zdolsek Draksler & Sirec, 2021).…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%
See 1 more Smart Citation